Determination of the relationship between soil structure and botanical composition of the plain pastures in the coastal region of Samsun province - Mut H.; Ayan I.; Acar Z.; Basaran U.; Tongel O.; Onal Asci O. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
This study was conducted in 14 different plain pastures representative of the Samsun coastal Region. The relationships between soil structure and plant cover and distribution of the plants according to their families were studied in these pastures. Observations and measurements were made between 26th April and 17th May, 2005. Generally, Organic Matter (OM) contents were high in the clay soil pastures, moderate in the silty soil pastures, and moderate and low in the sandy soil pastures. pH values varied from 7.2 to 8.7. Plant cover of the pastures changed between 35.62 and 84.80%. Regarding the plant families, it was observed that silty soil pastures had more legumes and sandy soil pastures had plants belonging to the other families. However, no relationship could be determined between soil structure and sward botanical composition.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)